Profil Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII pada Materi Sistem Persamaan Linear Dua Variabel Ditinjau dari Gaya Kognitif - Shodiq, Lukman Jakfar; Apritasona, Warsosi (Kadikma, 2021)
The purpose of this study was to describe the problem-solving ability of eighth-grade junior high school students in terms of cognitive style in solving two-variable linear equations. This research is a descriptive study using a qualitative approach. The subjects of this study were students of class VIII SMPN 1 Senduro, namely four students from each of two different types of cognitive styles. Collecting data using questionnaires, test methods, and interview methods. According to Polya, there are four steps in the problem-solving ability of students, namely understanding, planning, implementing, and re-checking. The results showed that students with a field-dependent cognitive style had difficulty in analyzing a problem because they could not apply the four Polya problem solving while the field independent type cognitive style was very able to apply the four problem-solving steps according to Polya, namely, understanding, planning, implementing, and doing recheck.